Additive Differential Double Pulse Voltammetry Applied to the Study of Multistep Electron Transfer Reactions with Microelectrodes of Different Geometries - Molina, A; Gonzalez, J; Laborda, E; Compton, R (2012)
Additive differential double pulse voltammetry (ADDPV) is applied to the study of reversible multistep electron transfers at microelectrodes of different geometries, including discs, (hemi)spheres, bands and cylinders. Analytical expressions are deduced for arbitrary numbers of electrons transferred and for any difference between the formal potentials of the different redox couples. ADDPV curves show two or more peaks and one or more crossing potentials depending on the number of steps, the difference between the formal potentials and the pulse amplitude employed. The variation of the voltammograms with the electrode size and shape, the pulse amplitude and the difference between formal potentials is described. The optimal extraction of the values of the formal potentials from the ADDPV signal is also described. In this context, the use of the crossing potentials is particularly valuable since they can be measured with better accuracy than peak parameters and they are independent of experimental variables like the electrode geometry and size. © 2012 by ESG.